2013
DOI: 10.1186/1756-3305-6-46
|View full text |Cite
|
Sign up to set email alerts
|

Comparative field evaluation of combinations of long-lasting insecticide treated nets and indoor residual spraying, relative to either method alone, for malaria prevention in an area where the main vector is Anopheles arabiensis

Abstract: BackgroundLong-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS) are commonly used together in the same households to improve malaria control despite inconsistent evidence on whether such combinations actually offer better protection than nets alone or IRS alone.MethodsComparative tests were conducted using experimental huts fitted with LLINs, untreated nets, IRS plus untreated nets, or combinations of LLINs and IRS, in an area where Anopheles arabiensis is the predominant malaria vector spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 57 publications
2
106
1
Order By: Relevance
“…A study performed in experimental huts in Tanzania that tested several IRS compounds used concomitantly with LLINs showed IRS with DDT or pyrethroids did not confer additional value to LLINs alone, but showed IRS with OPs could be effective in preventing blood feeding and increasing vector mortality when combined with LLINs (Okumu et al, 2013). These studies suggest there may be value in adding a nonpyrethroid insecticide paint, insecticide treated plastic sheetings or IRS to LLINs.…”
Section: Tablementioning
confidence: 95%
“…A study performed in experimental huts in Tanzania that tested several IRS compounds used concomitantly with LLINs showed IRS with DDT or pyrethroids did not confer additional value to LLINs alone, but showed IRS with OPs could be effective in preventing blood feeding and increasing vector mortality when combined with LLINs (Okumu et al, 2013). These studies suggest there may be value in adding a nonpyrethroid insecticide paint, insecticide treated plastic sheetings or IRS to LLINs.…”
Section: Tablementioning
confidence: 95%
“…Results from experimental huts indicate that there is no additional benefit of using IRS if LLIN are in use 14 except where pyrethroid-resistant vectors occur, in which case a non-pyrethroid insecticide sprayed on the walls provides additional protection 15,16 . However, a recent analysis of survey data from 17 African countries indicated these concerns might be unwarranted since using LLIN and IRS together was associated with lower malaria prevalence than LLIN alone 17 and a review of non-randomized studies indicated that addition of LLIN to IRS was associated with lower parasite rates than IRS alone 6 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent studies of residual transmission systems where highly endophagic mosquitoes have been effectively tackled by IRS or LLINs remind us that behavioral avoidance of indoor insecticide exposure, by such a naturally evasive species as An. arabiensis, 6,7,34,35 does not necessarily represent failure, or even waning impact, of these measures but rather their inherent limitations from the outset. 18,[31][32][33][36][37][38] Recent reports of surprising 39 and previously undescribed 40 primary vectors most probably does not reflect the emergence of new vector systems but rather that their role in transmission is now more obvious because they are no longer outnumbered by An.…”
mentioning
confidence: 99%